Vascular Calcification in an Adolescent Treated with Long-Term Peritoneal Dialysis - Mesiha Ekim; Suat Fitoz; Z. Birsin Ozcakar; Fatos Yalcinkaya (International Journal of Nephrology)
The reason of high mortality in patients with chronic kidney disease (CKD) is cardiovascular disease and arterial calcification has been accepted as an additive factor on this status. In this report we described vascular and cardiac valvular calcifications in an adolescent on CAPD.